Oral creatine in hemodialysis patients increases physical functional capacity and muscle mass, an open label study - Waldo Bernales-Delmon; Simón Schulz; Iván Guglielmi; Cynthia Saravia; Yasna Venegas; Jaime Joost; Jose Aguilar; Andrés Wulf; Paulina Bittner; María Claudia Martínez; Sandy Gómez; Catalina Chávez; et al. (PLoS ONE, 2025)
Background and hypothesis Individuals undergoing chronic hemodialysis represent a population with high morbidity and mortality, primarily due to poor nutritional status, chronic inflammation, and cardiovascular disease. However, additional factors, such as low physical activity and impaired functionality, have also been identified as directly associated with increased mortality. Main objective This study was conceived as a pilot study to investigate whether creatine supplementation (5g/day) for eight weeks could provide benefits in terms of physical functionality, handgrip and body composition in a group of adult patients on chronic hemodialysis. On dialysis days, creatine was administered immediately post-dialysis, while on non-dialysis days, patients took the supplement at home. Measurements were taken using bioimpedance analysis, handgrip strength (via dynamometry), and the Short Physical Performance Battery (SPPB), both before starting creatine supplementation and at week 8 of treatment. Results After performing robust statistical analysis, following creatine supplementation, an increase in SPPB scores was observed, with a mean improvement of 0.78 points [95% CI: 0.17–1.44] and an effect size of 0.53. Skeletal muscle mass increased by an average of 1.31 kg [95% CI: 0.55 to 2.23], with an effect size of 0.66. Fat-free mass showed a mean increase of 2.11 kg [95% CI: 0.75 to 3.58] with an effect size of 0.64, while phase angle rose by 0.52 degrees [95% CI: 0.27 to 0.76], corresponding to an effect size of 0.90. Regarding volumetric estimates, total body water increased by 1.17 L [95% CI: 0.26 to 2.13] with an effect size of 0.54, and intracellular water increased by 0.97 L [95% CI: 0.48 to 1.51] with an effect size of 0.81. No significant differences were observed in extracellular water with change of 0.20 L [95% CI: −0.30 to 0.70] or handgrip strength with an increment of 0.67 kgF, [95% CI: −0.67 to 2.11]. Conclusion Oral creatine supplementation in HD patients for eight weeks improved muscular and functional outcomes and may be proposed as a strategy to mitigate the elevated morbidity observed in this group of patients.